ETF yearbook 2012 : evaluation and monitoring of vocational education and training systems and the role of evidence-based policy in their reforms - (:unkn) unknown (Publications Office of the European Union, 2012)
"There is a high demand for methods and instruments that enable VET experts to analyse and evaluate education and training systems, recognise strengths and weaknesses as well as to identify possible areas for development and to monitor improvement. The over-arching aim of this Yearbook is therefore to take stock of such approaches, methods and instruments and to provide an opportunity for mutual exchange of experience and an in-depth discussion with the partner countries." "The Yearbook will place a key focus on the Torino Process review strategy and analyse and assess the overall approach, the methodology and main findings from the exercise carried out in 2010." "The ETF Torino Process is an analytical exercise that informs policy making in vocational education and training (VET) and related policy learning processes in the ETF's partner countries in the Southern Mediterranean, Eastern and South Eastern Europe as well as Central Asia." (Textauszüge, BIBB-Doku)
Keywords: Berufsbildungspolitik; Berufsbildungssystem; Reform; Monitoring; Evaluation; Internationale Beziehungen; Jahrbuch